Evaluation Of The Implementation Of The Duty Of The Pamong Praja Police Unit In Enforcing Regional Regulations Pekanbaru City (Night Club Business Supervision Study) - Ahmad Fitra Yuza; Centi Wardana (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2022)
From year to year nightclubs in Pekanbaru grow rapidly. such as being dissatisfied with the permits that have been given to the nightclub businessmen, which clearly violates Article 5 of Regional Regulation No. 3 of 2002. In the regionalregulation it is emphatically stated that the operating hours of entertainment venues in Pekanbaru City, but in reality currently almost all clubs Evenings in Pekanbaru City are closed in the early hours of the morning and some are evenuntil dawn. however, there is no firm stance taken by the Pekanbaru City Government regarding this violation. Not only that, night clubs business people also commit violations such as allowing nightclubs, being a place for transactions and the use of illegal drugs, selling liquor, providing women as entertainers, carrying out prostitution activities and becoming a gambling place. The purpose of this study is to determine the evaluation of the implementation of the duties of the CivilService police units in enforcing the Pekanbaru City Regional Regulation and its obstacles. The methods used are descriptive and qualitative methods; The informants in this study were Satpol PP personnel and night club owners. Data collection techniques are observations and interviews. the the results of the study are the ineffectiveness of night club supervision carried out by the Satpol PP because even though it is prohibited to operate, the night club remains open so that it is increasingly disturbing for people who gather. the obstacles found in this study are the absences of regulations that specifically regulate night clubs and weak coordination.